2020
DOI: 10.7150/ijms.42005
|View full text |Cite
|
Sign up to set email alerts
|

Induction Chemotherapy Improved Long Term Outcomes in Stage IV Locoregional Advanced Nasopharyngeal Carcinoma

Abstract: We aimed to determine whether adding induction chemotherapy (IC) to concurrent chemoradiation (CCRT) improved outcomes in each stage of locally advanced nasopharyngeal carcinoma (LANPC). Methods: From 2007 to 2013, we retrospectively collected 259 histopathologically identified adult LANPC patients from two campuses in south Taiwan. Among the 238 eligibly treated cases, 156 patients received CCRT (CCRT group) upfront and 82 received IC followed by CCRT (IC group). Of these patients, 130 were stage III (92 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Great progress has been made in clinical trials of this disease and the NCCN guidelines have been rewritten (12). Conversely, biomarker research based on liquid biopsies is lagging, especially in the fields of proteomics and metabolomics, which limits the advancement of relevant research to a certain extent (7)(8)(9)(13)(14)(15)17,100,124,125). For example, IC, as a standard initial method for systemic treatment of LA-NPC, the results of clinical trials show that not all patients can benefit from its use (15).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…Great progress has been made in clinical trials of this disease and the NCCN guidelines have been rewritten (12). Conversely, biomarker research based on liquid biopsies is lagging, especially in the fields of proteomics and metabolomics, which limits the advancement of relevant research to a certain extent (7)(8)(9)(13)(14)(15)17,100,124,125). For example, IC, as a standard initial method for systemic treatment of LA-NPC, the results of clinical trials show that not all patients can benefit from its use (15).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Compared with CCRT alone, the prognosis of a considerable number of LA-NPC patients has not been significantly improved due to the addition of IC, indicating that they have suffered unnecessary over treatment ( 22 ). Conversely, in those who have extended the survival by IC+CCRT, 20-30% patients with LA-NPC still present tumor relapse and metastasis, suggesting that the current clinical application of IC may also provide insufficient treatment ( 13 , 14 ). Therefore, it is urgent to identify molecular biomarkers to predict the short-term efficacy of IC.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical diagnosis has identified that COVID-19 patients have similar indications to other coronavirus affected patients, e.g. MERS and SARS [6]. The initial indication of COVID-19 infection is cough, fever, and short breath, and in the late stage, it can damage the kidney, cause pneumonia, and unexpected death.…”
Section: Introductionmentioning
confidence: 99%